2003
DOI: 10.1091/mbc.e03-03-0169
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of Specific Tropomyosin Isoforms in Gastrointestinal Epithelial Cells and Their Impact on CFTR at the Apical Surface

Abstract: Microfilaments have been reported to be polarized in a number of cell types based both on function and isoform composition. There is evidence that microfilaments are involved in the movement of vesicles and the polarized delivery of proteins to specialized membrane domains. We have investigated the composition of actin microfilaments in gastrointestinal epithelial cells and their role in the delivery of the cystic fibrosis transmembrane conductance regulator (CFTR) into the apical membrane using cultured T84 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…We therefore conclude that Tm5a and Tm5b are the isoforms present in the cell periphery and ruffling membranes. This correlates well with the apical enrichment of these isoforms in epithelial cells (Dalby-Payne et al 2003). The WD4/9d antibody, which detects Tm4 and Tm1, was also predominantly found in stress fibers Equal loading (20 g) of total cellular protein isolated from mouse tissues was electrophoresed on 12.5% low-bis SDS gels, and individual blots were immunoblotted with (A) ␤-actin, (B) ␥-actin, and (C) ␣-smooth-muscle actin.…”
Section: Subcellular Localization Of Tm Isoforms In Cultured Mouse Prsupporting
confidence: 78%
“…We therefore conclude that Tm5a and Tm5b are the isoforms present in the cell periphery and ruffling membranes. This correlates well with the apical enrichment of these isoforms in epithelial cells (Dalby-Payne et al 2003). The WD4/9d antibody, which detects Tm4 and Tm1, was also predominantly found in stress fibers Equal loading (20 g) of total cellular protein isolated from mouse tissues was electrophoresed on 12.5% low-bis SDS gels, and individual blots were immunoblotted with (A) ␤-actin, (B) ␥-actin, and (C) ␣-smooth-muscle actin.…”
Section: Subcellular Localization Of Tm Isoforms In Cultured Mouse Prsupporting
confidence: 78%
“…For instance, Ostap and co-workers have shown that Myo1b, which is involved in organelle transport, does not recognize actin filaments that contain either Tpm1.6 (also known as Tm2) or Tpm3.1 (Tang and Ostap, 2001;Kee et al, 2015;McIntosh et al, 2015). In addition, Tpm1.8 (also known as Tm5a) and Tpm1.9 regulates the recycling of the cystic fibrosis transmembrane receptor (CFTR) (Dalby-Payne et al, 2003). Tpm1.8 and Tpm1.9 are enriched at apical sites, which are also enriched for CFTR, and depletion of Tpm1.8 and Tpm1.9 leads to elevated levels of CFTR in the apical membrane.…”
Section: Morphogenesismentioning
confidence: 99%
“…Colocalization is shown in c. Scale bar for all, 10 m. intracellular localization. Cytochalasin D treatment, for example, disintegrates the isoform-specific Tm localization pattern in several cell types (3,45). Therefore it is more likely that Tm proteins display a variant-specific intracellular localization via either their differential affinities for actin-binding proteins or actin isoforms (34).…”
Section: Discussionmentioning
confidence: 99%
“…Quick frozen tissue was homogenized in immunoprecipitation (IP) buffer (50 mM Tris·HCl pH 7.4, 1 mM EGTA, 50 mM NaCl, 3 mM MgCl 2, 1% Nonident P-40, 1% sodium deoxycholate, 3 mM ATP, 3 mM DTT, 67 M ZnCl2, 29.6 mM ␤-glycerophosphate, protease inhibitors) and then precleared with protein G-coupled dynabeads (Invitrogen). To reduce background, the antibodies used in this assay were cross-linked to protein G-coupled dynabeads (Invitrogen) using the cross-linking reagent Bis(sulfosuccinimidyl)suberate (BS 3) following the manufacturer's instructions. The precleared cell lysates were incubated for 16 h at room temperature with either the sheep polyclonal anti-Tm6 antibody (Sh X Tropomyosin) or the mouse monoclonal anti-Tm1 antibody [CG1; (7,15,16,28)], cross-linked to protein G-coupled dynabeads.…”
Section: Identification Of Tm Variants In Aorta Via Lc Ms/ms Analysismentioning
confidence: 99%